Borderline ovarian tumors: a study of 100 cases from Tertiary Care Hospital - Uysal, Ahmet; Mun, Semih; Uysal, Fatma; Öztekin, Murat; Büyüktosun, Cem; Șehirali, Salim; Bașoğul, Ömer; Taner, Cüneyt E. (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: The purpose of the study was to evaluate patients with borderline ovarian tumors. Material and methods: Clinical features, treatment and survival status of 100 patients with borderline ovarian tumors were retrospectively evaluated between 1998 and 2007. Results: Patients’ mean age was 37.75 years (range: 15–72); 22 of them were postmenopausal. Histopathological diagnoses were serous, mucinous, endometrioid and clear cell in 54%, 41%, 2% and 3% of the patients, respectively; 70 patients had stage IA disease, 8 were at stage IB, 16 at stage IC, 2 at stage IIIA, 3 at stage IIIB and 1 at stage IIIC. Restaging laparotomies were performed on 19 patients; fertility-sparing surgery was performed on 52 patients; 2 patients received chemotherapy because of advanced-stage disease. All patients are currently alive. The 5-year disease-free survival rate for 71 cases was 100%. Conclusions : Borderline ovarian tumors have excellent prognoses, and fertility-conserving surgery can be performed in young patients with early-stage disease.